Trade Protection and Firm Productivity: Evidence from Thai Manufacturing. (June 2017) - Jongwanich, Juthathip; Kohpaiboon, Archanun
Abstract : This paper examines the effect of trade protection on firm productivity, using the Thai manufacturing sector as a case study. While our main finding is in favor of a liberal trade policy environment, we argue input and output tariffs should be treated separately in examining their impact on productivity. Ceteris paribus, lowering input tariffs potentially has at least two opposite effects. It allows firms to benefit in several ways, enhancing their productivity, while also discouraging their efforts to improve productivity due to the increased level of effective protection. This necessitates caution when pursuing trade policy reform in not placing too much focus on input tariffs while leaving output tariffs untouched. Even though input and output tariffs work differently in promoting firms' productivity, any trade policy reform process should take both input and output tariffs into consideration in ensuring that trade is actually liberalized.